Fumigant toxicity of some essential oils against Red Flour Beetles, Tribolium castaneum (Herbst) and its safety to mammals - Sileem,T. M. (2020)
Abstract Fumigant activities for three essential oils; Garlic oil (Allium sativum L); Chili pepper (Capsicum annuum L.) and Nigella (Nigella sativa L.) were assessed at different concentrations against the adult and 20-days old larval stages of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) in the laboratory. The accumulative mortality was observed at different exposure periods (3, 5 and 7 days). The residual effect of garlic oil that was the effective oil, on the treated wheat grains was evaluated with respect to histological changes in the liver, kidney, and stomach of rat fed on this treated wheat. The results showed that the mortality rates of treated stages increased with increasing the time of fumigation treatment. Moreover the highest essential oils toxicity at the Median lethal concentration (LC50) values for exposure periods (3, 5 and 7 days) to fumigation were (126, 53, and 47 mg/L air) for adult stage and were (79, 62, and 41 mg/L air) for larval stage, respectively in the case of Garlic oil treatment. While, the lowest essential oils effective was Nigella oil at the Median lethal concentration (LC50) values for exposure periods (3, 5 and 7 days) to fumigation were (3594, 629, and 335 mg/L air) for adult stage and were (1040, 416, and 227 mg/L air) for larval stage, respectively. The toxicity effect of various essential oils against adults and larvae of T. castaneum at the LC50at 7 days fumigation could be arranged in descending order as follows: Garlic oil, Chili pepper oil, and Nigella oil. The histological changes showed that the organs slightly affected at the fumigation for 3 days. It may be concluded that the garlic essential oil is the good effective fumigant to control T. castaneum in the stored products and it recommended that the fumigation period does not exceed 3 days. The garlic essential oil has the potential for applications in IPM programs for stored-grain pests because of its high volatility and fumigant activity and its safety.